Silicon-carbon composite material and preparation method thereof, secondary battery and electric device
By using a silicon-carbon composite material of a porous carbon matrix and a silicon-based material distributed in its pores in the secondary battery, the problem of insufficient circulation performance of the negative electrode active material in existing secondary batteries is solved, and higher circulation performance and first-time Coulomb efficiency are achieved.
Patent Information
- Application Number
- CN202410122765.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-29
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-01-29
AI Technical Summary
The performance of the negative electrode active material in existing secondary batteries cannot meet the requirements of high cycling performance.
A silicon-carbon composite material is used, which includes a porous carbon matrix and a silicon-based material, wherein at least a portion of the silicon-based material is distributed in the pores of the porous carbon matrix, satisfying the conditions of Q2/Q1≤0.7 to improve the cycling performance of the secondary battery.
By depositing the silicon-based material mainly in the pores of the porous carbon matrix, enrichment on the surface is reduced, and the cycling performance and first-time Coulomb efficiency of the secondary battery are significantly improved.
Smart Images

Figure CN119852344A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a silicon-carbon composite material and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As secondary batteries have made great progress, higher requirements have been put forward for their performance.
[0003] Silicon-carbon composite materials are usually used as negative electrode active materials for secondary batteries, which have an important impact on the performance of secondary batteries. However, in current secondary batteries, the performance of negative electrode active materials cannot meet the requirements of high cycle performance of secondary batteries. Summary of the invention
[0004] The present application is made in view of the above problems, and its purpose is to provide a silicon-carbon composite material and a preparation method thereof that can improve the cycle performance of a secondary battery. In addition, the present application also provides a secondary battery including the silicon-carbon composite and an electrical device including the secondary battery.
[0005] In order to achieve the above-mentioned objectives, the present application provides a silicon-carbon composite material and a preparation method thereof, a secondary battery and an electrical device.
[0006] In a first aspect, the present application provides a silicon-carbon composite material, the silicon-carbon composite material comprising:
[0007] A porous carbon matrix and a silicon-based material, wherein at least a portion of the silicon-based material is distributed in the pores of the porous carbon matrix;
[0008] And the silicon-carbon composite material satisfies Q2 / Q1≤0.7; wherein, the silicon-carbon composite material is charged and discharged by a button battery, and the capacity when the voltage increases from 0.2V to 0.4V during the charging process is Q1, and the capacity when the voltage increases from 0.4V to 0.6V during the charging process is Q2.
[0009] The silicon-carbon composite material in the present application satisfies Q2 / Q1≤0.7, which reflects that most of the silicon-based material is deposited in the pores of the porous carbon matrix, and only a small amount of silicon-based material is deposited on the surface of the porous carbon matrix, which can effectively improve the cycle performance of the secondary battery.
[0010] In some embodiments, the silicon-carbon composite material satisfies 0.3≤Q2 / Q1≤0.7. In some embodiments, the silicon-carbon composite material satisfies 0.5≤Q2 / Q1≤0.65.
[0011] In some embodiments, at least a portion of the surface of the silicon-carbon composite material has a coating layer; optionally, the coating layer has a thickness of 2 nm to 100 nm.
[0012] The silicon-carbon composite material of the present application has a coating layer on its surface, which can reduce the side reaction between the material surface and the electrolyte, thereby improving the first coulombic efficiency of the secondary battery.
[0013] In some embodiments, the silicon-carbon composite material satisfies Q3 / Q1≤0.37; wherein the capacity when the voltage is from 0.6V to 0.8V during the charging process is Q3.
[0014] Therefore, the silicon-carbon composite material of the present application satisfies Q3 / Q1≤0.37, and can effectively improve the first coulombic efficiency of the secondary battery.
[0015] In some embodiments, the silicon-carbon composite material satisfies 0.25≤Q3 / Q1≤0.37. In some embodiments, the silicon-carbon composite material satisfies 0.3≤Q3 / Q1≤0.37.
[0016] In some embodiments, the porous carbon matrix includes micropores and mesopores. In some embodiments, the pore volume ratio of the micropores to the mesopores is 1 to 40; in some embodiments, the pore volume ratio of the micropores to the mesopores is 3 to 10.
[0017] In some embodiments, the silicon-carbon composite material satisfies at least one of the following:
[0018] The specific surface area of the silicon-carbon composite material is 0.1 m 2 / g to 5m 2 / g, in some embodiments 1m 2 / g to 3m 2 / g;
[0019] The silicon-carbon composite material has a silicon-based material content of 30% to 60%, and in some embodiments, 40% to 50%;
[0020] The silicon-based material in the silicon-carbon composite material is at least partially present in the form of amorphous silicon.
[0021] In a second aspect, the present application provides a method for preparing a silicon-carbon composite material, the method comprising the following steps:
[0022] Passing a gas containing silane into a reactor containing the porous carbon substrate to deposit a silicon-based material in the pores of the porous carbon substrate;
[0023] Monitor the reaction exhaust gas, and when the volume concentration of silane in the reaction exhaust gas is not higher than 5 vol%, stop introducing the gas containing silane to obtain the silicon-carbon composite material, wherein the silicon-carbon composite material includes: a porous carbon matrix and a silicon-based material, wherein at least a portion of the silicon-based material is distributed in the pores of the porous carbon matrix, and the silicon-carbon composite material satisfies Q2 / Q1≤0.7; wherein a button battery is used to charge and discharge the silicon-carbon composite material, and the capacity when the voltage is from 0.2V to 0.4V during the charging process is Q1, and the capacity when the voltage is from 0.4V to 0.6V during the charging process is Q2.
[0024] In the preparation method of the present application, by monitoring the volume concentration of silane in the exhaust gas to be no higher than 5 vol%, the silicon-based material is deposited on the surface of the porous carbon matrix as little as possible, so that the silicon-carbon composite material satisfies Q2 / Q1≤0.7, thereby effectively improving the cycle performance of the secondary battery.
[0025] In some embodiments, the total volume of silane in the silane-containing gas introduced per kg of the porous carbon substrate is 400 L to 1500 L. In some embodiments, the total volume of silane in the silane-containing gas introduced per kg of the porous carbon substrate is 650 L to 850 L.
[0026] In some embodiments, the temperature of depositing the silicon-based material is between 450°C and 600°C; and / or the deposition time for each kilogram of the porous carbon matrix is between 1.2h and 37.5h; and / or the ventilation rate of the silane-containing gas is between 0.1L / min and 10L / min.
[0027] In some embodiments, the deposition time is 2.5 h to 20 h per kg of the porous carbon substrate at 510° C. to 560° C.
[0028] In some embodiments, depositing silicon-based materials in the pores of the porous carbon matrix includes an initial reaction, a middle reaction, and a final reaction. Calculated by the amount of silane introduced per kilogram of the porous carbon matrix, the amount of silane introduced at the initial reaction is 20L to 170L, the amount of silane introduced in the middle reaction is 390L to 680L, and the amount of silane introduced at the final reaction is 20L to 170L; optionally, calculated by the amount of silane introduced per kilogram of the porous carbon matrix, the amount of silane introduced at the initial reaction is 150L to 170L, the amount of silane introduced in the middle reaction is 420L to 490L, and the amount of silane introduced at the final reaction is 150L to 170L.
[0029] Therefore, the present application helps to make silane enter the pores of the porous carbon matrix as much as possible by controlling the amount of silane deposition at different stages of the reaction process of depositing silicon-based materials in the pores of the porous carbon matrix, thereby depositing silicon-based materials in the pores of the porous carbon matrix rather than on the surface; in addition, it is also beneficial to improve the utilization efficiency of silane.
[0030] In some embodiments, the method further comprises:
[0031] coating a carbon coating layer on at least a portion of the surface of the silicon-carbon composite material;
[0032] Optionally, coating at least a portion of the surface of the silicon-carbon composite material with a carbon coating layer comprises:
[0033] A gas containing a carbon source is introduced into the reactor, and the reaction is carried out at 550° C. to 900° C. for 0.5 to 10 hours; optionally, the reaction is carried out at 600° C. to 700° C. for 2 to 6 hours.
[0034] The present application forms a carbon coating layer on the surface of the silane composite material to obtain a silicon-carbon composite material with reduced surface activity, thereby reducing the side reaction between the silicon-carbon composite material and the electrolyte. The prepared silicon-carbon composite material satisfies Q3 / Q1≤0.37, which can effectively improve the first coulombic efficiency of the secondary battery.
[0035] In a third aspect, the present application provides a secondary battery, the secondary battery comprising a negative electrode plate, the negative electrode plate comprising the silicon-carbon composite material of the first aspect of the present application, or comprising a silicon-carbon composite material prepared by the method for preparing the silicon-carbon composite material of the second aspect of the present application. The secondary battery has excellent cycle performance.
[0036] In a fourth aspect, the present application provides an electrical device, wherein the electrical device comprises the secondary battery according to the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0038] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0039] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0040] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0041] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0042] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0043] Description of reference numerals:
[0044] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module; 5. Battery cell; 51. Shell; 52. Electrode assembly; 53. Top cover assembly. DETAILED DESCRIPTION
[0045] Hereinafter, the embodiments of the silicon-carbon composite material and its preparation method, secondary battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0046] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0047] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0048] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0049] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0050] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0051] Silicon-based materials have higher theoretical gram capacity than carbon-based materials, but silicon-based materials expand significantly during the battery charge and discharge cycle, resulting in unsatisfactory cycle life.
[0052] At present, silicon-based materials can be deposited into the pores of porous carbon matrix through chemical vapor infiltration to generate silicon-carbon composite materials, which can solve the problem of cycle life to a certain extent. Silicon-carbon composite materials are usually used as negative electrode active materials of secondary batteries and have an important influence on the performance of secondary batteries. In current secondary batteries, the performance of silicon-carbon composite materials used as negative electrode active materials cannot meet the requirements of high cycle performance of secondary batteries.
[0053] Based on this, the present application proposes a silicon-carbon composite material and a preparation method thereof, a secondary battery and an electrical device.
[0054] In a first aspect, the present application provides a silicon-carbon composite material, the silicon-carbon composite material comprising:
[0055] A porous carbon matrix and a silicon-based material, wherein at least a portion of the silicon-based material is distributed in the pores of the porous carbon matrix;
[0056] And the silicon-carbon composite material satisfies Q2 / Q1≤0.7; wherein, the silicon-carbon composite material is charged and discharged by a button battery, and the capacity when the voltage increases from 0.2V to 0.4V during the charging process is Q1, and the capacity when the voltage increases from 0.4V to 0.6V during the charging process is Q2.
[0057] The silicon-carbon composite material of the present application satisfies Q2 / Q1≤0.7, which reflects that most of the silicon-based material is deposited in the pores of the porous carbon matrix, and a small amount of silicon-based material is deposited on the surface of the porous carbon matrix, which can effectively improve the cycle performance of the secondary battery.
[0058] The silicon-carbon composite material is prepared into a button-type half-cell, and the button-type half-cell is used for charging and discharging. During the charging process, the capacity charged to 0.2V is recorded as C1, the capacity charged to 0.4V is recorded as C2, the capacity charged to 0.6V is recorded as C3, and the capacity charged to 0.8V is recorded as C4; wherein, during the charging process, the capacity from 0.2V to 0.4V is Q1 = (C2-C1), the capacity from 0.4V to 0.6V is Q2 = (C3-C2), and the capacity from 0.6V to 0.8V is Q3 = (C4-C3). In the technical solution of the present application, the silicon-carbon composite material satisfies Q2 / Q1≤0.7 to improve the cycle performance of the secondary battery. The above-mentioned button-type half-cell is composed of a working electrode using the silicon-carbon composite material provided in the present application as the negative electrode active material and a counter electrode composed of metallic lithium.
[0059] It should be noted that the phase transition of silicon in the silicon-carbon composite material during lithium insertion is relatively complex, and the phase transition during lithium insertion can be summarized as Si→Li x Si→Li 15 Si4, the delithiation process is the opposite, and the phase change during the delithiation process can be summarized as Li 15 Si4→Li x Si→Si, where x is a value between 0 and 15.
[0060] During the charging process of the button half-charger, Q1 corresponds to a charging capacity of 0.2V to 0.4V, which comes from the phase change of silicon in the pores inside the porous carbon matrix. 15 Si4→Li x Si; Q2 corresponds to a charge capacity of 0.4V to 0.6V, which comes from the phase transition of silicon on the surface of the porous carbon matrix. 15 Si4→Li x Si→Si, and the phase transition of silicon inside the porous carbon matrix to Li x Si→Si; Q3 corresponds to a charge capacity of 0.6V to 0.8V, which is derived from the delithiation phase transition of oxygen defects and LiSi x C y The corresponding value represents the capacity contributed by each phase transition. The larger the value, the higher the contributed capacity, and the higher the corresponding content of the phase.
[0061] Among these phase changes, it is mainly the silicon on the surface of the porous carbon matrix in Q2 that deteriorates the cycle performance of the silicon-carbon composite material. Therefore, in the process of depositing silicon, the silicon-based material should be deposited in the pores of the porous carbon matrix as much as possible to reduce the enrichment of the silicon-based material on the surface of the porous carbon matrix. In this way, the Q2 / Q1 of the silicon-carbon composite material can be reduced and its cycle life can be improved.
[0062] The silicon-carbon composite material provided by the present application includes a porous carbon matrix and a silicon-based material distributed in the pores of the porous carbon matrix. The porous carbon matrix can improve the conductivity of the silicon-based material, and can also serve as a buffer medium for the volume expansion of the silicon-based material during the charge and discharge process, effectively alleviating the problem of the volume enlargement of the secondary battery caused by the expansion of the silicon-based material. Furthermore, the silicon-carbon composite material satisfies Q2 / Q1≤0.7, which can effectively improve the cycle performance of the secondary battery.
[0063] In some embodiments, the silicon-carbon composite material satisfies 0.3≤Q2 / Q1≤0.7. In further embodiments, the silicon-carbon composite material satisfies 0.5≤Q2 / Q1≤0.65.
[0064] The silicon-carbon composite material meets the corresponding range of Q2 / Q1, which is more conducive to improving the cycle performance of the secondary battery. For example, Q2 / Q1 can be 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63 and 0.64.
[0065] In some embodiments, at least part of the surface of the silicon-carbon composite material has a coating layer. Optionally, the coating layer has a thickness of 2nm to 100nm. The present application has no particular restrictions on the thickness of the coating layer, and can be adjusted according to actual needs. For example, the coating layer thickness can be 5nm to 90nm, 10nm to 80nm, 20nm to 80nm, 20nm to 60nm, etc., specifically 10nm, 20nm, 30nm, 40nm, 50nm, etc.
[0066] It should be noted that the Q3 capacity comes from the delithiation phase transition of oxygen defects and LiSi x C y After the silicon-carbon composite material is deposited, the activity of the silicon-based material is very high. The Q3 / Q1 of the silicon-carbon composite material can be reduced by forming a coating layer on the surface of the silicon-carbon composite material to reduce the reaction activity of the material surface, thereby improving the first coulombic efficiency of the secondary battery.
[0067] It should be noted that the coating layer can be a continuous and complete coating layer or an incomplete coating layer. "Continuous and complete" means that the entire surface of the silicon-carbon composite material is coated by the coating layer. "Incomplete" means that at least part of the surface of the silicon-carbon composite material is coated by the coating layer.
[0068] According to a specific embodiment, the coating layer is a carbon coating layer.
[0069] In some embodiments, the powder resistivity of the silicon-carbon composite material with a carbon coating layer at 4 MPa is less than 50 Ω·cm. The silicon-carbon composite material has excellent electrical conductivity, which helps to improve the kinetic performance of the secondary battery.
[0070] In some embodiments, the silicon-carbon composite material satisfies Q3 / Q1≤0.37; wherein the capacity when the voltage is from 0.6V to 0.8V during the charging process is Q3.
[0071] The silicon-carbon composite material satisfies Q3 / Q1≤0.37, and can effectively improve the first coulombic efficiency of the secondary battery.
[0072] In some embodiments, Q3 / Q1 of the silicon-carbon composite material may be greater than 0.37, for example, 0.38, 0.40, 0.42, 0.44, etc.
[0073] In some embodiments, the silicon-carbon composite material satisfies 0.25≤Q3 / Q1≤0.37. Alternatively, the silicon-carbon composite material satisfies 0.3≤Q3 / Q1≤0.37.
[0074] The silicon-carbon composite material meets the corresponding range of Q3 / Q1, which is more conducive to improving the first coulombic efficiency of the secondary battery. For example, Q3 / Q1 can be 0.25, 0.28, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36 and 0.37, but is not limited thereto.
[0075] In some embodiments, the porous carbon matrix includes micropores and mesopores; optionally, a pore volume ratio of the micropores to the mesopores is 1 to 40; optionally, 3 to 10.
[0076] The porous carbon matrix includes pores of different pore sizes. For example, the porous carbon includes micropores, which refer to pores with a pore size of less than 2nm (usually 0.5nm to 2nm). For another example, the porous carbon includes mesopores, which refer to pores with a pore size range of 2nm to 50nm. When the pore volume ratio of the micropores and mesopores of the porous carbon matrix is within the above range, it can provide a suitable space for the deposition of silicon-based materials, so that the silicon-carbon material has a suitable capacity.
[0077] Exemplarily, the pore volume of the micropores and mesopores of the porous carbon matrix can be tested by methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method according to GB / T19587-2017, and calculated by BET method, wherein the nitrogen adsorption specific surface area analysis test can be performed by TriStar 3020 specific surface area pore size analysis tester of Micromeritics, USA.
[0078] In some embodiments, the silicon-carbon composite material satisfies at least one of the following:
[0079] The specific surface area of the silicon-carbon composite material is 0.1 m 2 / g to 5m 2 / g; optionally 1m 2 / g to 3m 2 / g;
[0080] The silicon-based material content in the silicon-carbon composite material is 30% to 60%; optionally, 40% to 50%;
[0081] The silicon-based material in the silicon-carbon composite material is at least partially present in the form of amorphous silicon.
[0082] Exemplarily, the specific surface area of the silicon-carbon composite material is a well-known meaning in the art and can be tested by methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method according to GB / T19587-2017 and calculated by BET method, wherein the nitrogen adsorption specific surface area analysis test can be performed by Tri Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.
[0083] For example, the content of silicon-based material in the silicon-carbon composite material can be tested by inductively coupled plasma atomic emission spectroscopy (ICP-AES).
[0084] In a second aspect, the present application provides a method for preparing the above silicon-carbon composite material, the method comprising the following steps:
[0085] Passing a gas containing silane into a reactor containing the porous carbon substrate to deposit a silicon-based material in the pores of the porous carbon substrate;
[0086] The reaction tail gas is monitored, and when the volume concentration of silane in the reaction tail gas is not higher than 5 vol%, the introduction of the gas containing silane is stopped to obtain the silicon-carbon composite material.
[0087] The present application controls the amount of silicon-based material deposited on the surface of the porous carbon matrix by controlling the volume concentration of silane in the reaction tail gas to be no higher than 5 vol% during the process of depositing silicon-based material in the pores of the porous carbon matrix, and then stops introducing the gas containing silane to obtain the silicon-carbon composite material. Thus, the prepared silicon-carbon composite material satisfies Q2 / Q1≤0.7, so that most of the silicon-based material is deposited in the pores of the porous carbon matrix, and as little silicon-based material as possible is enriched on the surface of the porous carbon matrix, which can effectively improve the cycle performance of the secondary battery.
[0088] The volume concentration of silane in the reaction tail gas can be monitored by any conventional method, or by using a commercially available silane detection instrument. It should be understood that under normal process conditions, a small amount of unreacted silane gas (e.g., a volume concentration of less than 0.01 vol%) will be discharged from the tail gas. At this time, the reaction is still in progress, and it is not necessary to stop the introduction of the gas containing silane.
[0089] In some embodiments, the total volume of the silane in the gas containing silane is 400L to 1500L per kilogram of the porous carbon substrate. Optionally, the total volume of the silane in the gas containing silane is 650L to 850L per kilogram of the porous carbon substrate. Exemplarily, the total volume of the silane in the gas containing silane is 650L, 680L, 700L, 720L, 750L, 780L, 800L, 820L, 840L, etc. per kilogram of the porous carbon substrate. The total volume of the silane in the gas containing silane can be determined according to the amount of silicon to be deposited, and the present application has no particular limitation on this.
[0090] In the technical solution of the present application, in the process of depositing silicon-based materials in the pores of the porous carbon matrix, the total amount of silane introduced is an important process parameter. For each kilogram of porous carbon matrix, the total amount of silane introduced depends on the gas flow range of the gas containing silane and the duration of the reaction. Therefore, the present application is more conducive to making the prepared silicon-carbon composite material meet Q2 / Q1≤0.7 by limiting the total amount of silane introduced, thereby effectively improving the cycle performance of the secondary battery.
[0091] The silane-containing gas described herein includes, in addition to silane, a carrier gas, which is usually an inert gas such as nitrogen.
[0092] In some embodiments, the volume concentration of silane in the silane-containing gas ranges from greater than 5 to 100 vol%, optionally from 20 vol% to 80 vol%. Exemplarily, the volume concentration of silane in the silane-containing gas is 20 vol%, 30 vol%, 40 vol%, 50 vol%, 60 vol%, 70 vol%, 80 vol%.
[0093] According to a specific embodiment, the silane is monosilane.
[0094] The present application does not have any particular limitation on the volume concentration range of silane in the silane-containing gas, and any conventional volume concentration range of silane may be used.
[0095] In some embodiments, the temperature of depositing the silicon-based material is between 450°C and 600°C; and / or, the deposition time for each kilogram of the porous carbon matrix is between 1.2 hours and 37.5 hours; and / or, the ventilation rate of the silane-containing gas is between 0.1 L / min and 10 L / min. Optionally, at 510°C to 560°C, the deposition time for each kilogram of the porous carbon matrix is between 2.5 hours and 20 hours.
[0096] The present application does not have any special limitation on the gas flow rate range of silane in the gas containing silane, and any conventional gas flow rate range of silane is acceptable. Exemplarily, the ventilation rate of the gas containing silane is in the range of 0.8L / min to 8L / min, 1L / min to 6L / min, 2L / min to 8L / min or 3L / min to 6L / min. More specifically, the ventilation rate of the gas containing silane is 0.8L / min, 1L / min, 2L / min, 3L / min, 3.5L / min, 4L / min, 4.5L / min, 5L / min, 6L / min, 8L / min, etc.
[0097] Exemplarily, the temperature of depositing the silicon-based material ranges from 500° C. to 560° C., 510° C. to 550° C., 520° C. to 550° C., or 520° C. to 540° C. More specifically, the temperature of depositing the silicon-based material is 480° C., 490° C., 500° C., 510° C., 515° C., 520° C., 525° C., 530° C., 535° C., 540° C., 550° C., 560° C., 570° C., etc.
[0098] Under the conditions of different determined reaction temperatures, ventilation rates and the proportion of silane in the silane-containing gas, the method of the present application can terminate the reaction in time by monitoring the silane content in the exhaust gas, avoiding excessive silicon deposition on the surface of the carbon matrix, thereby reducing the Q2 / Q1 value.
[0099] In the technical solution of the present application, in the process of depositing silicon-based materials in the pores of the porous carbon matrix, the deposition temperature and reaction time are important process parameters. Generally, the higher the deposition temperature, the shorter the reaction time. Of course, the determination of the reaction endpoint still depends on when the volume concentration of silane in the reaction tail gas can be monitored to be no higher than 5 vol%.
[0100] In some embodiments, depositing the silicon-based material in the pores of the porous carbon matrix includes an initial reaction, a middle reaction, and a final reaction. The amount of silane introduced per kilogram of the porous carbon matrix is 20 L to 170 L in the initial reaction, 390 L to 680 L in the middle reaction, and 20 L to 170 L in the final reaction. In some specific embodiments, the amount of silane introduced per kilogram of the porous carbon matrix is 150 L to 170 L in the initial reaction, 420 L to 490 L in the middle reaction, and 150 L to 170 L in the final reaction.
[0101] The reaction process of depositing silicon-based materials in the pores of porous carbon matrix is divided into the initial stage of reaction, the middle stage of reaction and the final stage of reaction. In the initial stage of reaction, the inner and outer surfaces of silicon-based materials and porous carbon matrix form silicon-carbon interface, and the reaction speed is slow. At this time, if the amount of silane introduced in the early stage of reaction is large, the utilization rate of silane is low. In the final stage of reaction, the reaction of depositing silicon-based materials in the pores of porous carbon matrix gradually reaches saturation. At this time, if the amount of silane introduced in the final stage of reaction is large, silane is more likely to be deposited on the surface of porous carbon matrix rather than being deposited in the pores of porous carbon matrix. Therefore, the amount of silane introduced in the initial stage of reaction and the final stage of reaction is less than the amount of silane introduced in the middle stage of reaction.
[0102] Therefore, the present application divides the reaction process of depositing silicon-based materials in the pores of the porous carbon matrix, which is beneficial to improving the utilization efficiency of silane.
[0103] In some specific embodiments, the deposition amount of the silicon-based material in the pores of the porous carbon matrix at the initial reaction, the middle reaction, and the final reaction can be controlled by controlling the deposition time, the concentration of silane, the flow rate, etc. to control the amount of silane introduced in each period. For example, based on the total duration of the deposition of the silicon-based material, the duration of the initial reaction accounts for 10% to 20%, the duration of the middle reaction accounts for 60% to 80%, and the duration of the final reaction accounts for 10% to 20%. Among them, the volume concentration of silane at the initial reaction and the final reaction can be controlled to be less than the volume concentration of silane at the middle reaction, and / or the gas flow rate of the gas containing silane at the initial reaction and the final reaction can be controlled to be less than the gas flow rate of the gas containing silane at the middle reaction.
[0104] In some embodiments, during the process of depositing the silicon-based material in the pores of the porous carbon matrix, the pressure in the reactor ranges from greater than 0 to 1 kPa; optionally, from 100 Pa to 500 Pa.
[0105] The present application does not have any special limitation on the reaction pressure, and the pressure during the deposition process can be a slightly positive pressure.
[0106] In some embodiments, the method further comprises:
[0107] coating a carbon coating layer on at least a portion of the surface of the silicon-carbon composite material;
[0108] Optionally, coating at least a portion of the surface of the silicon-carbon composite material with a carbon coating layer comprises:
[0109] A gas containing a carbon source is introduced into the reactor, and the reaction is carried out at 550° C. to 900° C. for 0.5 to 10 hours; optionally, the reaction is carried out at 600° C. to 700° C. for 2 to 6 hours.
[0110] In a specific embodiment, after the introduction of the silane-containing gas is stopped, the reactor does not need to be replaced, and a gas containing a carbon source is immediately introduced into the reactor for surface coating.
[0111] Therefore, the present application forms a carbon coating layer on the surface of the silane composite material to obtain a silicon-carbon composite material. At this time, the prepared silicon-carbon composite material satisfies Q3 / Q1≤0.37, which can effectively improve the first coulombic efficiency of the secondary battery.
[0112] In some embodiments, the carbon source is selected from at least one of the following: methane, ethylene, acetylene and propane.
[0113] The present application has no particular limitation on the choice of carbon source, and any conventional carbon source may be used.
[0114] In some embodiments, the volume concentration of the carbon source in the gas containing the carbon source ranges from greater than 0 to 100 vol%; the volume concentration of the carbon source can optionally range from 20 vol% to 80 vol%.
[0115] The present application does not have any particular limitation on the volume concentration range of the carbon source in the gas containing the carbon source, and any conventional volume concentration range of the carbon source may be used.
[0116] In some embodiments, the gas flow rate of the carbon source in the gas containing the carbon source ranges from greater than 0.1 L / min to 10 L / min; the gas flow rate of the carbon source can optionally range from greater than 0.1 L / min to 4 L / min.
[0117] The present application does not have any particular limitation on the gas flow rate range of the carbon source in the gas containing the carbon source, and any conventional gas flow rate range of the carbon source may be used.
[0118] In a third aspect, the present application provides a secondary battery, the secondary battery comprising a negative electrode plate, the negative electrode plate comprising the silicon-carbon composite material of the first aspect of the present application, or comprising a silicon-carbon composite material prepared by the method for preparing the silicon-carbon composite material of the second aspect of the present application. The secondary battery has excellent cycle performance.
[0119] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0120] In one embodiment of the present application, a secondary battery is provided.
[0121] The term "secondary battery" mentioned herein refers to a battery cell, a battery module or a battery pack, which are described below.
[0122] Generally, a secondary battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0123] Negative electrode
[0124] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material, and the negative electrode active material may include the silicon-carbon composite material of the first aspect of the present application.
[0125] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0126] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0127] In some embodiments, the negative electrode active material may further adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may further include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys.
[0128] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0129] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0130] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0131] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0132] Positive electrode
[0133] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0134] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0135] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0136] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.1 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0137] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0138] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0139] In some embodiments, when the battery cell is a sodium ion battery, the positive electrode active material may be a positive electrode active material for a sodium ion battery known in the art. As an example, the positive electrode active material may include sodium transition metal oxides, polyanionic compounds (phosphates, fluorophosphates, pyrophosphates, sulfates), Prussian blue compounds, etc. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used.
[0140] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1. For example, sodium iron composite oxide (NaFeO2), sodium cobalt composite oxide (NaCoO2), sodium chromium composite oxide (NaCrO2), sodium manganese composite oxide (NaMnO2), sodium nickel composite oxide
[0141] (NaNiO2), sodium nickel titanium composite oxide (NaNi 1 / 2 Ti 1 / 2 O2), sodium nickel manganese composite oxide (NaNi 1 / 2 Mn 1 / 2O2), sodium iron manganese composite oxide (Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2), sodium nickel cobalt manganese composite oxide (NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2).
[0142] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n- valence state.
[0143] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n-A class of compounds containing anion units and halogen anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; the halogen may be at least one of F, Cl and Br.
[0144] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.
[0145] Polyanionic compounds include NaFePO4, Na3V2(PO4)3, NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).
[0146] The Prussian blue compound may be a compound having sodium ions, transition metal ions and cyanide ions (CN-). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The Prussian blue compound may be, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0 <a≤2,0<b<1,0<c<1。
[0147] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0148] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0149] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0150] Electrolytes
[0151] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0152] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0153] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0154] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0155] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0156] Isolation film
[0157] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0158] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0159] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0160] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0161] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0162] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0163] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0164] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0165] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0166] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0167] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0168] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0169] In a fourth aspect, the present application provides an electrical device, wherein the electrical device comprises the secondary battery according to the third aspect of the present application.
[0170] The secondary battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0171] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0172] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0173] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0174] Example
[0175] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0176] Preparation of Silicon Carbon Composite Materials
[0177] Example 1
[0178] a. Place 1 kg of porous hard carbon matrix (the pore volume ratio of micropores to mesopores is 6.5) in a rotary kiln, heat it to 500 ° C under nitrogen protection and keep it for 2 hours to fully desorb the air adsorbed in the porous carbon matrix;
[0179] b. Vacuum the rotary kiln to a vacuum degree of 1×10 -5 Pa, maintain the pressure for 5 minutes and then introduce nitrogen until the pressure in the kiln returns to normal;
[0180] c. Repeat step b until the oxygen content in the exhaust gas is less than 200ppm;
[0181] d. A mixed gas of monosilane and nitrogen is introduced, the mixed gas ratio is monosilane: nitrogen = 1:4, the ventilation rate is 4L / min, the kiln is maintained at a slightly positive pressure of 200Pa, and the rotary kiln rotation frequency is 40Hz;
[0182] e. The concentration of monosilane in the reaction tail gas was monitored by a chromatograph (model: Agilent Lab Gc 8860). When the introduction of the mixed gas of monosilane and nitrogen was stopped, the concentration of monosilane in the reaction tail gas was 4.8 vol%, and the total amount of monosilane introduced was 780 L;
[0183] f. Raise the temperature in the rotary kiln to 600°C, introduce a mixed gas of acetylene and nitrogen for 5 hours, the ratio of the mixed gas is acetylene: nitrogen = 1:4, the ventilation rate is 2L / min, a slight positive pressure of 200Pa is maintained in the kiln, and the rotation frequency of the rotary kiln is 40Hz to obtain a silicon-carbon composite material having a carbon coating layer with a thickness of about 10nm; wherein the total amount of acetylene introduced is 600L.
[0184] Example 2
[0185] The silicon-carbon composite material of Example 2 was prepared similarly to Example 1, except that the total amount of monosilane introduced was 720 L; and when the introduction of the mixed gas of monosilane and nitrogen was stopped, the concentration of monosilane in the reaction tail gas was 2.5 vol%.
[0186] Example 3
[0187] The silicon-carbon composite material of Example 3 was prepared similarly to Example 1, except that the ventilation rate of the mixed gas of monosilane and nitrogen was 3.8 L / min, and when the ventilation of the mixed gas of monosilane and nitrogen was stopped, the concentration of monosilane in the reaction exhaust gas was 3.7 vol%.
[0188] Example 4
[0189] The silicon-carbon composite material of Example 4 was prepared similarly to Example 1, except that no carbon coating layer was formed on the surface of the silicon-carbon composite material, and when the introduction of the mixed gas of monosilane and nitrogen was stopped, the concentration of monosilane in the reaction exhaust gas was 4.7 vol%.
[0190] Comparative Example 1
[0191] The silicon-carbon composite material of Comparative Example 1 was prepared similarly to Example 1, except that when the introduction of the mixed gas of monosilane and nitrogen was stopped, the concentration of monosilane in the reaction tail gas was 5.5 vol%.
[0192] Preparation of button cells
[0193] The negative electrode sheet was prepared according to the following method: the silicon-carbon composite material, conductive agent carbon black, and binder polyacrylic acid prepared above were mixed in a mass ratio of 8:1:1, deionized water solvent was added, and the mixture was stirred with a rapid mixer until the system was uniform to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on the negative electrode current collector copper foil and dried at 85°C, and the negative electrode sheet was obtained after cold pressing.
[0194] The electrolyte was prepared as follows: ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were mixed in a volume ratio of 20:20:60, LiPF6 was uniformly dissolved in the above solution, and an additive fluoroethylene carbonate (FEC) was added to obtain an electrolyte. The concentration of LiPF6 was 1 mol / L, and the mass proportion of FEC in the electrolyte was 5%.
[0195] The button battery is prepared according to the following method: the above-mentioned negative electrode plate is used as the working electrode, the metallic lithium is used as the counter electrode, and the polypropylene film is used as the isolation membrane. The negative electrode plate, the isolation membrane and the metallic lithium are stacked in order so that the isolation membrane is between the working electrode and the counter electrode, and the electrolyte is injected to assemble the button battery.
[0196] Preparation of secondary batteries
[0197] The negative electrode sheet is prepared according to the following method: the negative electrode active material (the silicon-carbon composite material prepared above is mixed with artificial graphite in a ratio of 1:9), the conductive agent carbon nanotube and SP mixture, the binder styrene-butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in an appropriate amount of solvent deionized water in a weight ratio of 95.5:1:2:1.5 to form a negative electrode slurry. The negative electrode slurry is coated on both surfaces of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.
[0198] The positive electrode sheet was prepared by the following method: the positive electrode active material LiNi 0.8 Co 0.l Mn 0.1 O2 (NCM811) is mixed with conductive carbon black and polyvinylidene fluoride in a weight ratio of 97.5:1.2:1.3, and an appropriate amount of solvent NMP is added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.
[0199] The electrolyte was prepared according to the following method: a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) was used as an organic solvent, wherein the volume ratio of EC, EMC and DEC was 20:20:60. In an oxygen atmosphere glove box with a water content of <10ppm, a fully dried lithium salt (LiPF6) was dissolved in the above organic solvent, and an additive fluoroethylene carbonate (FEC) was added to obtain an electrolyte. In the electrolyte, the concentration of LiPF6 was 1 mol / L, and the mass proportion of FEC in the electrolyte was 5%.
[0200] Polypropylene film is used as the isolation membrane.
[0201] The secondary battery is prepared according to the following method: the positive electrode sheet, separator and negative electrode sheet prepared above are placed in order, the separator (i.e., polypropylene film) is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then the electrode assembly is obtained by winding; the electrode assembly is placed in an outer package, and after drying, the electrolyte prepared above is injected, and the secondary battery is obtained through vacuum packaging, standing, formation, capacity division and other processes.
[0202] Button cell battery performance test
[0203] 1. Q2 / Q1 and Q3 / Q1
[0204] After the button cell prepared above was left to stand for 60 minutes, it was discharged to 5 mV at 0.05C constant current, discharged to 5 mV at 50μA, left to stand for 10 minutes, and charged to 0.8 V at 0.1C for testing. The capacity when the voltage changes from 0.2V to 0.4V during the charging process is recorded as Q1, the capacity when the voltage changes from 0.4V to 0.6V is recorded as Q2, and the capacity when the voltage changes from 0.6V to 0.8V is recorded as Q3, and Q2 / Q1 and Q3 / Q1 are calculated.
[0205] 2. The first coulombic efficiency test
[0206] After the button battery assembled above was left standing for 60 minutes, it was discharged to 5mV using a constant current of 0.05C, discharged to 5mV using 50μA, left standing for 10 minutes, and charged to 0.8V using 0.1C for testing, wherein the lithium desorption capacity of 0.8V represents the capacity of the silicon-carbon composite material, corresponding to the lithium desorption capacity / lithium insertion capacity when the first effect = 0.08V.
[0207] Performance test of secondary batteries
[0208] Cycle performance test
[0209] At 25°C, the secondary battery is left to stand for 30 minutes, then charged to 4.25V at a rate of 0.5C, further charged to a current of 0.05C at a constant voltage of 4.25V, left to stand for 5 minutes, and then discharged to a voltage of 2.5V at a rate of 0.5C. The resulting capacity is recorded as the initial capacity C0. This is a charge and discharge cycle. Repeat the above steps for the same secondary battery, and record the discharge capacity Cn during each cycle. The battery capacity retention rate after each cycle is Pn = Cn / C0*100%, until Pn≦80%, stop the test, and record the number of cycles at this time.
[0210] For the button cells prepared in Examples 1 to 4 and Comparative Example 1, Q2 / Q1, Q3 / Q1 and first coulombic efficiency were tested; for the secondary batteries prepared in Examples 1 to 4 and Comparative Example 1, the cycle performance was tested, and the specific results are shown in Table 1.
[0211] Table 1
[0212]
[0213] As shown in Table 1, by controlling the silicon-carbon composite material to satisfy Q2 / Q1≤0.7, the cycle life of the secondary battery is significantly improved.
[0214] Example 5
[0215] The silicon-carbon composite material of Example 5 was prepared similarly to Example 1, except that the deposition temperature was 450° C. and the introduction of the mixed gas of monosilane and nitrogen was stopped, and the concentration of monosilane in the reaction tail gas was 3.4 vol%.
[0216] Example 6
[0217] The silicon-carbon composite material of Example 6 was prepared similarly to Example 1, except that the deposition temperature was 520° C. and when the introduction of the mixed gas of monosilane and nitrogen was stopped, the concentration of monosilane in the reaction tail gas was 3.4 vol%.
[0218] Example 7
[0219] The silicon-carbon composite material of Example 7 was prepared similarly to Example 1, except that the deposition temperature was 550° C. and when the introduction of the mixed gas of monosilane and nitrogen was stopped, the concentration of monosilane in the reaction tail gas was 3.4 vol%.
[0220] Example 8
[0221] The silicon-carbon composite material of Example 8 was prepared similarly to Example 1, except that the deposition temperature was 600° C. and when the introduction of the mixed gas of monosilane and nitrogen was stopped, the concentration of monosilane in the reaction tail gas was 3.4 vol%.
[0222] For the button cells prepared by the silicon-carbon composite materials prepared in Examples 5 to 8 according to the same method as above, Q2 / Q1, Q3 / Q1 and first coulombic efficiency were tested. For the secondary batteries prepared by the silicon-carbon composite materials prepared in Examples 5 to 8 according to the same method as above, the cycle performance was tested. The specific results are shown in Table 2.
[0223] Table 2
[0224] serial number Deposition temperature Q2 / Q1 Q3 / Q1 First coulombic efficiency Number of cycles Example 1 500℃ 0.691 0.362 93.4% 2539 Example 5 450℃ 0.695 0.363 93.2% 2550 Example 6 520℃ 0.664 0.362 93.5% 2671 Example 7 550℃ 0.681 0.361 93.3% 2639 Example 8 600℃ 0.696 0.363 93.1% 2543
[0225] As shown in Table 2, as the deposition temperature changes, the Q2 / Q1 of the button cell made of silicon-carbon composite materials will also change, and the corresponding cycle performance of the secondary battery made of silicon-carbon composite materials will also change. In general, the deposition temperature has little effect on the cycle performance of the secondary battery made of silicon-carbon composite materials.
[0226] Example 9
[0227] The silicon-carbon composite material of Example 9 was prepared similarly to Example 1, except that the amount of monosilane introduced at the initial stage of the reaction was 155 L, the amount of monosilane introduced at the middle stage of the reaction was 470 L, and the amount of monosilane introduced at the end of the reaction was 155 L; and when the introduction of the mixed gas of monosilane and nitrogen was stopped, the concentration of monosilane in the reaction exhaust gas was 2.3 vol%.
[0228] Example 10
[0229] The silicon-carbon composite material of Example 10 was prepared similarly to Example 1, except that the amount of monosilane introduced at the initial stage of the reaction was 170 L, the amount of monosilane introduced at the middle stage of the reaction was 440 L, and the amount of monosilane introduced at the end of the reaction was 170 L; and the introduction of the mixed gas of monosilane and nitrogen was stopped, and the concentration of monosilane in the reaction exhaust gas was 2.3 vol%.
[0230] The button cells prepared from the silicon-carbon composite materials prepared in Example 9 and Example 10 by the same method as above were tested to obtain the first coulombic efficiency. The secondary cells prepared from the silicon-carbon composite materials prepared in Example 9 and Example 10 by the same method as above were tested to obtain the cycle performance. The specific results are shown in Table 3.
[0231] Table 3
[0232]
[0233] As shown in Table 3, the reaction process is divided into the initial stage of the reaction, the middle stage of the reaction and the final stage of the reaction. As the amount of monosilane introduced in each reaction stage changes, the Q2 / Q1 of the button battery prepared from the silicon-carbon composite material will also change, and the corresponding cycle performance of the secondary battery prepared from the silicon-carbon composite material will also change. In general, dividing the reaction process into three stages and controlling the amount of monosilane introduced in each reaction stage is more conducive to controlling the Q2 / Q1 of the button battery prepared from the silicon-carbon composite material within an optional range.
[0234] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material comprises: a porous carbon matrix and a silicon-based material, wherein at least part of the silicon-based material is distributed in the pores of the porous carbon matrix; And the silicon-carbon composite material satisfies Q2 / Q1≤0.7; wherein, the silicon-carbon composite material is charged and discharged by a button battery, and the capacity when the voltage increases from 0.2V to 0.4V during the charging process is Q1, and the capacity when the voltage increases from 0.4V to 0.6V during the charging process is Q2.
2. The silicon-carbon composite material according to claim 1, characterized in that: The silicon-carbon composite material satisfies 0.3≤Q2 / Q1≤0.7; optionally, 0.5≤Q2 / Q1≤0.
65.
3. The silicon-carbon composite material according to claim 1 or 2, characterized in that: At least part of the surface of the silicon-carbon composite material has a coating layer; optionally, the coating layer has a thickness of 2 nm to 100 nm.
4. The silicon-carbon composite material according to claim 3, characterized in that: The silicon-carbon composite material satisfies Q3 / Q1≤0.37; wherein, during the charging process, the capacity when the voltage increases from 0.6V to 0.8V is Q3.
5. The silicon-carbon composite material according to claim 4, characterized in that: The silicon-carbon composite material satisfies 0.25≤Q3 / Q1≤0.37; optionally, 0.3≤Q3 / Q1≤0.
37.
6. The silicon-carbon composite material according to any one of claims 1 to 5, characterized in that: The porous carbon matrix includes micropores and mesopores; optionally, a pore volume ratio of the micropores to the mesopores is 1 to 40.
7. The silicon-carbon composite material according to any one of claims 1 to 6, characterized in that: The silicon-carbon composite material satisfies at least one of the following: The specific surface area of the silicon-carbon composite material is 0.1 m 2 / g to 5m 2 / g; The silicon-based material content in the silicon-carbon composite material is 30% to 60%; The silicon-based material in the silicon-carbon composite material is at least partially present in the form of amorphous silicon.
8. A method for preparing a silicon-carbon composite material, characterized in that: The method comprises the following steps: Passing a gas containing silane into a reactor containing the porous carbon substrate to deposit a silicon-based material in the pores of the porous carbon substrate; Monitor the reaction exhaust gas, and when the volume concentration of silane in the reaction exhaust gas is not higher than 5 vol%, stop introducing the gas containing silane to obtain the silicon-carbon composite material, wherein the silicon-carbon composite material includes: a porous carbon matrix and a silicon-based material, wherein at least a portion of the silicon-based material is distributed in the pores of the porous carbon matrix, and the silicon-carbon composite material satisfies Q2 / Q1≤0.7; wherein a button battery is used to charge and discharge the silicon-carbon composite material, and the capacity when the voltage is from 0.2V to 0.4V during the charging process is Q1, and the capacity when the voltage is from 0.4V to 0.6V during the charging process is Q2.
9. The preparation method according to claim 8, characterized in that: The total volume of the silane introduced into the gas containing silane is 400 L to 1500 L per kilogram of the porous carbon substrate.
10. The preparation method according to claim 8 or 9, characterized in that: The temperature of depositing the silicon-based material is between 450° C. and 600° C.; and / or, The deposition time for each kilogram of the porous carbon substrate is 1.2 hours to 37.5 hours; and / or, The ventilation rate of the silane-containing gas is 0.1 L / min to 10 L / min; Optionally, the deposition temperature is 510° C. to 560° C., and the deposition time is 2.5 h to 20 h per kilogram of the porous carbon substrate.
11. The preparation method according to any one of claims 8 to 10, characterized in that: The deposition of silicon-based materials in the pores of the porous carbon matrix includes an initial reaction, a middle reaction and a final reaction. Calculated by the amount of silane introduced per kilogram of the porous carbon matrix, the amount of silane introduced in the initial reaction is 20L to 170L, the amount of silane introduced in the middle reaction is 390L to 680L, and the amount of silane introduced in the final reaction is 20L to 170L; optionally, calculated by the amount of silane introduced per kilogram of the porous carbon matrix, the amount of silane introduced in the initial reaction is 150L to 170L, the amount of silane introduced in the middle reaction is 420L to 490L, and the amount of silane introduced in the final reaction is 150L to 170L.
12. The preparation method according to any one of claims 8 to 11, characterized in that: The method further comprises: coating a carbon coating layer on at least a portion of the surface of the silicon-carbon composite material; Optionally, coating at least a portion of the surface of the silicon-carbon composite material with a carbon coating layer comprises: A gas containing a carbon source is introduced into the reactor, and the reaction is carried out at 550° C. to 900° C. for 0.5 to 10 hours; optionally, the reaction is carried out at 600° C. to 700° C. for 2 to 6 hours.
13. A secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises the silicon-carbon composite material according to any one of claims 1 to 7, or comprises the silicon-carbon composite material prepared by the preparation method according to any one of claims 8 to 12.
14. An electrical device, characterized in that: The electric device comprises the secondary battery as claimed in claim 13.
Citation Information
Patent Citations
Novel materials with extremely durable intercalation of lithium and manufacturing methods thereof
CN108475779A
Silicon-carbon composite material and preparation method thereof, secondary battery and electric device
CN117096330A
Silicon carbon material and preparation method thereof, negative electrode material, negative electrode plate, battery and electric device
CN117334869A
Die bonding system and die bonding method using the same
KR102817649B1
PRODUCTION METHOD OF Si-C COMPOSITE
WO2022250169A1
Cited By
Preparation method for preparing carbon-based silicon composite negative electrode material and double-cone rotary fluidization device
CN121361793A